THE ROLE OF TEACHERS IN ENHANCING STUDENTS' UNDERSTANDING OF FIQH MATERIAL AT MA MUALLIMIN NW GUNUNG RAJAK - Niken Hafizah (Formad English Foundation NTB-Jakarta, 2024)
This study investigates the role of teachers in enhancing students' understanding of Fiqh material at MA Muallimin NW Gunung Rajak. This study used a descriptive quantitative approach The research design was a survey, with data collected through questionnaires. The data were analyzed using descriptive quantitative methods, calculating frequencies and percentages for each student response. The findings reveal that 85% of students appreciated the detailed explanations and relatable examples provided by teachers, which facilitated the practical application of Fiqh in daily life. Furthermore, 78% of students reported increased motivation due to their teachers' active encouragement. Effective teaching strategies identified included group discussions (82%), question-and-answer sessions (76%), and contextual approaches (70%). Supporting factors such as student motivation (83%), engaging learning media (75%), and varied teaching methods (80%) significantly enhanced the learning process. However, challenges such as limited instructional time (67%) and insufficient learning resources (60%) were noted, affecting the overall effectiveness of Fiqh instruction. The study highlights the importance of pedagogical competence in religious education, recommending the integration of additional learning resources and extended instructional time to address existing challenges. These findings provide valuable insights for educators and school administrators in improving the quality of Fiqh education.